MODUL IPA TERPADU BERBASIS INQUIRY LEARNING PADA MATERI ZAT ADITIF MAKANAN UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS - PATIMAH, SITI; SIREGAR, TIURLINA; LUMBU, ALBERT; SAMOSIR, HOTLAN (Jurnal Ilmu Pendidikan Indonesia, 2021)
This study aims to find out how to make an integrated science module, develop an integrated science module, Â and improve science process skills by using an integrated science module based on inquiry learning on food additives. Research Methods Research and Development. The research sample was conducted in class VIII A SMP Negeri 1 Sentani with a total of 32 students. The results showed that: 1) How to make a module through seven stages, namely module needs analysis, module design, implementation, assessment, evaluation, validation and quality assurance of the module, using four module components, namely the opening, introduction, learning and evaluation. 2) The development of an integrated science module based on inquiry learning on food additives material through the arrangement of stages of making modules for the use of the school environment Very feasible category to be used as teaching material and 3) Assessment of students' science process skills in RPP 1 to RPP 3 learning produces an average percentage of 69.75% with the skilled category.